Research of suspension cooligomerization of unsaturated hydrocarbons of C9 fraction, initiated by organic peroxides - Оробчук, Оксана Михайлівна; Фуч, Уляна Василівна; Субтельний, Роман Олександрович; Дзіняк, Богдан Остапович (Eastern-European Journal of Enterprise Technologies, 2013)
The issue of processing by-products of ethylene production - liquid pyrolysis products, is of current importance. Industrial methods of initiated cooligomerization of unsaturated hydrocarbons of С9 fraction have several disadvantages, such as high temperature level and reaction duration, high cooligomer color indexes. In order to eliminate the above mentioned difficulties it was proposed to conduct cooligomerization in suspension. Suspension cooligomerization of unsaturated hydrocarbons of C9 fraction is a technologically initiated oligomerization in drops of monomer, dispersed in an aqueous medium mostly. Water-soluble stabilizers are used for suspension stabilizing. As a result of experimental studies, the dependence of physical and chemical properties of cooligomer on the initiator nature was given, the optimal ratio of suspension components and cooligomerization duration were set. The influence of various stabilizers on physical and chemical properties of cooligomer was studied. It was proposed to extract cooligomer from oligomerizate using the precipitation method. The results are of practical interest for processing by-products of diesel fuel pyrolysis.